Who cares? Provision of Care and Assistance Among Older Persons in the Philippines. (December 2018) - Abalos, Jeofrey B.; Saito, Yasuhiko; Cruz, Grace T.; Booth, Heather
Objective: This study aims to examine the provision of assistance among older persons in the Philippines who experience difficulty with activities of daily living (ADLs) or instrumental activities of daily living (IADLs).Method: Data for this research are drawn from the 2007 Philippine Study on Aging (PSOA). Cross-tabulations and regression analyses are used to identify who provides assistance to older Filipinos.Results: The study shows that the Filipino family, particularly spouse and daughters, plays an important role in providing assistance to older Filipinos who need help in carrying out functional activities. This provision of caregiving, however, follows a gendered pattern. Specifically, the spouse provides assistance to older men, whereas daughters provide assistance to older women. Grandchildren and noncoresident family members, to some extent, are also active in providing care to older Filipinos.Discussion: The Filipino family remains faithful to its filial duty toward older persons, but who provides care and the way it is provided are likely to change due to the demographic changes and values shifts that have swept the country.